The Future in Learning Science: What’s in it for the Learner?
XV, 299 p. 11 illus.
Keywords: This volume considers the future of science learning - what is being learned and how it is being learned - in formal and informal contexts for science education. To do this, the book explores major contemporary shifts in the forms of science that could or should be learned in the next 20 years, what forms of learning of that science should occur, and how that learning happens, including from the perspective of learners. In particular, this volume addresses shifts in the forms of science that are researched and taught post-school – emerging sciences, new sciences that are new integrations, “futures science”, and increases in the complexity and multidisciplinarity of science, including a multidisciplinarity that embraces ways of knowing beyond science. A central aspect of this in terms of the future of learning science is the urgent need to engage students, including their non-cognitive, affective dimensions, both for an educated citizenry and for a productive response to the ubiquitous concerns about future demand for science-based professionals. Another central issue is the actual impact of ICT on science learning and teaching, including shifts in how students use mobile technology to learn science.